First endemic arachnid from Isla Sala y Gómez (Motu Motiro Hiva), Chile: a new species of tube-dwelling spider (Araneae: Segestriidae) - Giroti, André Marsola; Cotoras, Darko D.; Lazo, Pedro; Brescovit, Antonio Domingos (European Journal of Taxonomy, 2020)
The Isla Sala y Gómez or Motu Motiro Hiva is located 415 km northeast of Rapa Nui (Easter Island) and 3420 km from the coast of northern Chile. It is a small oceanic island (2.5 km2) dominated by volcanic rock with very little vegetal cover. Here, we describe the first endemic arachnid for the island, Ariadna motumotirohiva sp. nov. Females are similar to those of Ariadna perkinsi Simon, 1900 from Hawaiʻi and Ariadna lebronneci Berland, 1933 from the Marquesas in the dorsal dark abdominal pattern, but they differentiate from the latter in the anterior receptaculum, promarginal cheliceral teeth and leg IV macrosetae. A recent survey of the arachnid fauna of Rapa Nui, which included Motu Nui and the rocky shores, did not record the presence of the family Segestriidae, neither has it been found during previous surveys. However, it is not possible to discard the possibility of a local extinction on Rapa Nui and survival on Sala y Gómez. This study suggests other endemic terrestrial arthropods could be present on this very small and remote island.